Village Government Strategy In Implementation of Village Farming Road Infrastructure Development In Tanah Bumbu Regency, Indonesia - Yulian Setiawan; Muhammad Anshar Nur; Tutung Nurdiyana (Wadah Inovasi Indonesia, 2022)
Strategy optimization of village government in the implementation of road infrastructure development of farming carried out in the village of Manurung District of Kusan Middle Tanah Bumbu which has carried out the authors conclude that it is less than optimal. This is because budgeting is not efficient in terms of where the development is carried out, and there is no role and contribution from the community in agricultural road infrastructure development activities both in planning, implementation, and supervision. This is the inability of the village apparatus to implement and manage government in the village in infrastructure development activities which are local government programs, there is no community empowerment in the ADD program which is a problem in optimizing the infrastructure development of the Manurung Village farm road. Supporting and inhibiting factors in carrying out the strategy in implementing farm road infrastructure development in Manurung Village, Kusan Tengah District, Tanah Bumbu Regency, it can be concluded that the supporting factors in the development of village infrastructure are participation and support from the community, adequate APBD funding to carry out development, as well as regulations given to villages to make managing their area easier. While the inhibiting factors for the development of village road infrastructure, it can be concluded that there are several things, namely firstly, the supervision and monitoring of infrastructure development have not been maximized, then the weather and rough terrain make the infrastructure development process difficult and take a long time, as well as construction materials that are increasingly expensive causing cost overruns. out of the calculation